Development and Validation of HPLC-FLD Analysis of Perampanel in MEPS-Processed Rat Plasma Sample - Ayah Nader Abu-shark; Ashok K. Shakya; Safwan M. Al-Adwan; Rajashri R. Naik (Separations, 2024)
Perampanel, a novel α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor antagonist, is registered for the adjunctive treatment of patients (aged ≥ 12 years) with refractory partial-onset seizures. A simple high-performance liquid chromatographic method fluorescence detection (HPLC-FLD) was developed to analyze perampanel in rats’ plasma and validated for bioanalytical purposes. Rats’ plasma (50 µL) was processed by microextraction packed sorbent (MEPS). The analytes were separated using a Hypersil Gold octadecyl silane column (250 × 4.6 mm internal diameter, 5 μm particle size) with isocratic elution. A mobile phase consisting of acetonitrile–methanol–water (275:275:450, v/v/v; containing 50 µL triethylamine and pH adjusted to 3.25 with orthophosphoric acid) was used in this analysis. The flow rate was 1.25 mL/min. Analytes were monitored at an excitation wavelength of 285 nm and an emission wavelength of 430 nm. The linearity range for this validated method was from 3.75 to 300 ng/mL. No endogenous peaks were found in the elution of analytes in drug-free rats’ plasma. Intra- and inter-batch reproducibility studies demonstrated accuracy and precision within the acceptance criteria. The results indicate that the present method is simple, selective, reproducible, and suitable for the analysis of perampanel in small volume samples. The robustness of the method was accessed using MODDE® design of experiments software version 12.5.